The Role of Media in Enhancing English Language Proficiency: A Systemic Literature Review - Adib fatoni; Mislawiyadi (MIDA : Jurnal Pendidikan Dasar Islam, 2026)
This article presents a comprehensive Systemic Literature Review on the role of media in enhancing English language proficiency. Drawing on 35 scholarly studies published between 2010 and 2024, the review explores how various types of media—including audiovisual materials, mobile-assisted tools, social media platforms, and digital applications—facilitate language development in EFL and ESL contexts. The findings reveal that media not only provides authentic input and multimodal exposure but also fosters learner engagement, autonomy, and motivation. Media has been shown to significantly improve listening, speaking, reading, and writing skills when integrated purposefully into language instruction. Through thematic analysis, the review categorizes media use into key areas such as skill-specific enhancement, informal learning, and technology-supported pedagogy. Despite the promising outcomes, challenges such as digital literacy gaps, access inequality, and lack of teacher training remain critical concerns. The paper concludes by emphasizing the pedagogical implications of media integration, urging educators, curriculum developers, and policymakers to adopt informed strategies that align media use with language learning objectives. Suggestions for future research and instructional practices are also provided to support more effective and inclusive media-enhanced language education.